Penerapan Metode Pembelajaran Kooperatif Tipe Think-Pair-Share dalam Pengajaran Pendidikan Agama Islam di SMP YPMA Medan - Shaiful Darmawan Sihotang (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This study aims to analyze the implementation of the Think-Pair-Share (TPS) cooperative learning method in the teaching of Islamic Religious Education (PAI) at SMP YPMA Medan. The problem addressed is the low level of active student participation in PAI learning. To address this issue, the TPS method was implemented as a strategy to increase student engagement. This research used a qualitative method with a descriptive approach. Data collection was carried out through observation, interviews, and documentation. The results showed that the application of the TPS method significantly increased student activity in discussions and collaboration, as well as deepened their understanding of the learning material. Students were more motivated and actively participated in the learning process, showing improvement in academic achievement. These findings indicate that the TPS method is effective in teaching PAI, particularly in facilitating interactive and collaborative learning.